Expected Transmission Energy Route Metric for Wireless Mesh Senor Networks - YanLiang Jin; HuiJun Miao; Quan Ge; Chi Zhou (International Journal of Digital Multimedia Broadcasting)
Mesh is a network topology that achieves high throughput and stable intercommunication. With great potential, it is expected to be the key architecture of future networks. Wireless sensor networks are an active research area with numerous workshops and conferences arranged each year. The overall performance of a WSN highly depends on the energy consumption of the network. This paper designs a new routing metric for wireless mesh sensor networks. Results from simulation experiments reveal that the new metric algorithm improves the energy balance of the whole network and extends the lifetime of wireless mesh sensor networks (WMSNs).